(3GdJTQjY GdVQjHj GdeUQj (B:s (3VQGFH GdMcheI GdeQcRjI Ydi ONhd GdGTNGU GdWHjYjjf habG dCMcGe GdVQjHI GdehMOI (B/s - (3MTjT, YGOd GMeOs ((3GdGRGQjWI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2001)
(3HGH JegjOi(B: (3eaGgje heQJcRGJ CSGSjI dGReI dOQGSI CMcGe GdVQjHI GdehMOI GdeHMK GdChd(B: (3eOi GSJbdGd GdbhGfjf GdefXeI ddVQGFH heUGOQ GdbGfhf GdVQjHi GdeHMK GdKGfi(B: (3eaghe eHOC bGfhfjI GdVQjHI hJWHjbGJg ai GdfXe GdVQjHjI GdeYGUQI GdeHMK GdKGdK(B: (3JaSjQ GdbGfhf GdVQjHi hJWHjbI ef MjK GdReGf hGdecGf GdeHMK GdQGHY(B: (3UdI GdbGfhf GdVQjHi HGdSjGSI GdVQjHjI hVQhQI JbjO CMcGeg HGdeHGOF GdOSJhQjI GdeJYdbI HGdYOGdI hGdeSGhGI ai JMed GdJcGdja hGdCYHGA GdeGdjI GdHGH GdChd(B: (3eYGde GdeYGedI GdVQjHjI GdebQQI Ydi ONd GdCTNGU GdWHjYjjf habkG dCMcGe GdVQjHI GdehMOI GdeHMK GdChd(B: (3GdNUGFU GdYGeI GdeejRI ddVQjHI GdehMOI GdeHMK GdKGfi(B: (3GdVQjHI GdehMOI VQjHI eaQhVI CSGSkG Ydi GdCTNGU GdWHjYjjf GdeHMK GdKGdK(B: (3bhGYO Jcdja GdTNU GdWHjYi HGdVQjHI HhUag TQjckG ai TQcGJ GdCTNGU heOi JejRgG Yf GdbhGYO GdeWHbI Ydi Gdeehd GdaQO GdeHMK GdQGHY(B: (3GdVQjHI GdehMOI VQjHI Ydi ONd GdaQO Ce Ydi GdONd GdCSQi ai eLehYI GdeHMK GdNGeS(B: (3fWGb SQjGf GdVQjHI GdehMOI ef MjK GdecGf (B((3GdeYGjjQ GdeWHbI ai ENVGY Gdecdajf ddVQjHI(B) (3GdeHMK GdSGOS(B: (3GdEWGQ GdRefi dSQjGf GdVQjHI GdehMOI (B( (3eHOC SfhjI GdJcdja hGSJbdGd GdSfhGJ GdVQjHjI(B) (3GdeHMK GdSGHY(B: (3EjQGOGJ QDhS GdCehGd GdefbhdI GdNGVYI ddVQjHI GdehMOI GdeHMK GdKGef(B: (3EjQGOGJ GdfTGW GdJLGQi hGdUfGYi GdNGVY dCMcGe GdVQjHI GdehMOI GdeHMK GdJGSY(B: (3EjQGOGJ GdeQJHGJ heG ai McegG GdNGVYI dCMcGe GdVQjHI GdehMOI GdeHMK GdYGTQ(B: (3EjQGOGJ Gdegf ZjQ GdJLGQjI GdNGVYI ddVQjHI GdehMOI GdeHMK GdMGOi YTQ(B: (3EjQGOGJ GdKQhI GdYbGQjI GdOGNdI ai fWGb hYGA GdVQjHI GdeHMK GdKGfi YTQ(B: (3GdCMcGe GdYGeI ddVQjHI GdehMOI GdHGH GdKGfi(B: (3GdCMcGe GdeJYdbI HGdLhGfH GdELQGFjI daQV hLHGjI GdVQjHI GdehMOI Ydi ONd GdCTNGU GdWHjYjjf GdeHMK GdChd(B: (3MUQ GdeLeY GdVQjHi hGdEdJRGeGJ GdhGbYI Ydi YGJb GdeNGWHjf HCMcGe GdbGfhf GdeHMK GdKGfi(B: (3Mb GdEWdGY hSQ GdegfI hGdbhGYO GdefXeI dEYdGf Gdeehdjf hGdEYaGAGJ GdVQjHjI hQHW GdVQGFH GdebQQI GdeHMK GdKGdK(B: (3GdWYhf GdVQjHjI hGdbhGYO GdeJYdbI HJMUjd GdVQjHI hVeGfGJ GdJMUjd hGdYbhHGJ GdebQQIs
Keywords: (3GdJTQjY GdVQjHjs; (3VQjHI Ydi ONd GdaQOs